2007
DOI: 10.1016/j.neuropsychologia.2006.07.020
|View full text |Cite
|
Sign up to set email alerts
|

A parametric fMRI investigation of context effects in sensorimotor timing and coordination

Abstract: Mounting evidence suggests that information derived from environmental and behavioral sources is represented and maintained in the brain in a context-dependent manner. Here we investigate whether activity patterns underlying movements paced according to an internal temporal representation depend on how that representation is acquired during a previous pacing phase. We further investigate the degree to which context dependence is modulated by different time delays between pacing and continuation. BOLD activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 79 publications
(93 reference statements)
6
62
0
1
Order By: Relevance
“…A notable feature of this framework is its ability to uncover generic mechanisms common to different kinds of systems at different levels of observation. For instance, the same basic patterns of coordinated behavior and pattern dynamics (multistability, critical fluctuations accompanied by a temporary loss of stability, phase transitions, hysteresis and critical slowing down) have been observed within an individual as in studies of bimanual and single limb movement coordination, studies of sensorimotor coordination between an individual and the environment or between individuals (Jantzen & Kelso, 2007;Kelso, 1995;and Swinnen, 2002 for reviews). Here we investigate how the natural (uninstructed) social influence of one person on another evolves in real time and report two key findings: the first is that humans immediately and spontaneously coordinate their actions with each other when provided vision of the movements of the other's hand together with their own.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A notable feature of this framework is its ability to uncover generic mechanisms common to different kinds of systems at different levels of observation. For instance, the same basic patterns of coordinated behavior and pattern dynamics (multistability, critical fluctuations accompanied by a temporary loss of stability, phase transitions, hysteresis and critical slowing down) have been observed within an individual as in studies of bimanual and single limb movement coordination, studies of sensorimotor coordination between an individual and the environment or between individuals (Jantzen & Kelso, 2007;Kelso, 1995;and Swinnen, 2002 for reviews). Here we investigate how the natural (uninstructed) social influence of one person on another evolves in real time and report two key findings: the first is that humans immediately and spontaneously coordinate their actions with each other when provided vision of the movements of the other's hand together with their own.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, other neural systems are likely to be required for our task to be performed. Among them is the cerebellum which has been reported to play a key role in perceiving (Leube, Knoblich, Erb, Grodd, Bartels, & Kirchera, 2003) and timing one's movements (Ivry & Spencer, 2004;Jantzen, Oullier, Marshall, Steinberg & Kelso, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern was found for both unimanual and bimanual tapping, and it suggested a higher demand of motor timing in areas such as SMA when the external pacing signal was absent. Similarly, Jantzen, Oullier, Marshall, Steinberg, and Kelso (2007) found that significant activity in the prefrontal-parietal-temporal network-consisting of dorsal and ventral prefrontal cortex, middle temporal gyrus, and bilateral parietal lobes-was present only in continuation tapping, not in synchronized tapping. Activity in these areas is typically associated with various working memory manipulations, and the observed activity was interpreted as the increased demand on working memory for the temporal representation of stimuli when the pacing signal was switched off.…”
Section: Paced Versus Unpaced Tappingmentioning
confidence: 87%
“…(a) Areas associated with covert sensorimotor synchronization and a perceived beat (Grahn & Brett, 2007;Grahn & Rowe, 2013;Teki et al, 2011). (b) Areas associated with externally paced and self-paced tapping (Brown et al, 2006;Jantzen et al, 2007;Kornysheva & Schubotz, 2011). (c) Areas within 16 mm from the brain surface that are associated with antiphase versus in-phase tapping and with the complexity of the pacing signal (J.L.…”
Section: Rhythm and Beat Perceptionmentioning
confidence: 99%
“…Context can also help to inform the subject about potential changes in the meaning of stimuli and actions. The medial prefrontal cortex (mPFC) is involved in various forms of cognition that depend on spatial and contextual information, including context-based cognitive tasks (2-4), contextual fear conditioning (5), and context-induced drug relapse (6)(7)(8), and is believed to be an important node in the "context" network (1,(9)(10)(11)(12). These functions likely depend on reciprocal interactions with the hippocampus (13,14), an area that has a well-established role in spatial and contextual processing (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%